The Impact of Temperature and Antioxidants on Oxidation and The Formation of Trans Fatty Acids in Several Palm Oil Derivatives - Martua Haojahan Saragih; Saronom Silaban; Eddiyanto Eddiyanto (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
The quality of palm oil is strongly influenced by temperature. The oxidation of palm oil can be caused by high temperatures. The higher the storage temperature, the faster oxidation occurs. In this research, the temperature significantly affects the quality of several palm oil derivative products such as Palm Olein, Palm Stearin, Palm Kernel Oil, and Palm Kernel Stearin. Antioxidants are very effective in resisting the increase in the oxidation reaction of some palm oil commodities. With the addition of tertiary butylhydroquinone (TBHQ) or butylated hydroxytoluene (BHT), the increase in peroxide value, p-anisidine values, free fatty acid, color tends to be slower than without the addition of antioxidants. For PV, BHT was the most effective antioxidant for RPKOL at a 29.75% increase, RBDOL at 9.91%, and RBDST at 5.26% but for RPKS TBHQ was the most effective increase at 19.83%. For anisidine value, TBHQ+BHT was most effective for RPKOL with a 61.62% increase, TBHQ for RPKS with 76.76%, BHT for RBDOL and RBDST with 15.37% and 14.46%. In the FFA test, BHT was effective for RPKOL and RPKS with a percentage increase of 6.48% and 6.67%, but TBHQ was effective for RBDOL and RBDST to controlled FFA with an increase of 8.41% and 3.38%. In color testing, TBHQ proved to be the effective antioxidant for RPKOL and RBDOL, resulting in percentage increases of 8.71% and 2.13%, respectively. For RPKS, the combination of TBHQ and BHT was employed, resulting in no percentage increase (0%). Additionally, BHT at 3.85% was used for RBDST. At a temperature of 130°C, an oxidation process was observed, indicating the formation of an aldehyde compound. This was evidenced by the FT-IR spectrum, showing peaks at wave numbers 1760 cm⁻¹ (C=O of aldehyde) and 2900 cm⁻¹ (CH on aldehyde). In this research, we can also see the formation of trans fatty acids C18:1n9t in GC-FID's peak area